PROBLEMATIKA POLITIK IDENTITAS DI NEGARA DEMOKRASI - Ryan Fachryan Lesmana Putra, Muhammad Rosyid Ridho, (JUSTITIABLE - Jurnal Hukum, 2024)
Entering the political year, the phenomenon of identity politics will definitely start to be heard again. The phenomenon of identity politics is the nation's toughest challenge, because it will lead to national disintegration. Especially in democratic countries that have a multicultural culture like Indonesia. Based on this phenomenon, the author will conduct research related to the problems of identity politics in democratic countries. The aim of this research is to find out what the problems of identity politics are in democratic countries, especially Indonesia as a multicultural country. The method used in this research is qualitative, namely by explaining the phenomenon of identity politics. The approach used is a descriptive phenomenological approach. The data collection technique in this research is library research. The conclusion from this research is that identity politics is actually permitted, but in the right portion. However, in reality they are excessive and tend to spark conflict between religions, ethnicities and cultures. Identity politics can be a threat to democracy in Indonesia because political aspirations are only focused on one particular identity, thereby potentially eliminating other identities in society